The Relationship Betwen Knowledge Level Of The Covid-19 Vaccine On Interest In Participation In Covid-19 Vaccination In YARSI University Medical Faculty Students Batch 2019 And Its Review By Islamic View - DAFA ZENOBIA; Rika Ferlianti; Siti Maulidya Sari; Muhammad Arsyad (Junior Medical Journal, 2022)
KEYWORDS Vaccine, COVID-19, Pandemic, Medicine, IslamABSTRACT          Background: In 2020, the whole world is experiencing the Covid-19 pandemic. This virus originated in China, precisely in the city of Wuhan, China and was discovered at the end of December 2019. Indonesia was the first country in Southeast Asia to be in the first position of confirmed positive cases of Covid-19. Efforts to break the transmission line from the Covid-19 virus are not only by equalizing vaccination coverage, but also the need for knowledge.Method: This type of research is descriptive quantitative research with cross sectional. The sample in this study were students of the Faculty of Medicine, YARSI University Class of 2019 as many as 171 respondents. Data collection was carried out using a questionnaire to determine the level of knowledge and also the level of interest in student vaccination participation related to the use of the Covid-19 vaccine. The data analysis used in this research is univariate data analysis and bivariate data analysis.Results: The characteristics of the respondents in this study consisted of women (71.9%) and men (28.1%) taken from the class of 2019. In this study, the percentage of respondents who had a good level of knowledge was 96.5%, then for respondents who had sufficient knowledge level is 3% and respondents who have less knowledge level are 0.5%. For the percentage of respondents in the interest of participation, the positive interest rate is 99.5% and the negative interest rate is 0.5%. The results of the bivariate analysis test between students' knowledge and interest levels showed that the results of the Correlations p-value test were 0.788 where p 0.05Conclusion: Level of Knowledge About Covid-19 Vaccine and Interest in Participating in Covid Vaccination has a strong correlation.